Digital Competence and AI-TPACK of Lecturers: Implications for the Professional Development of Sports Education Lecturers - Afandi, Ahmad Afandi Harja; Asep Rahmat; Irpan (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
Evaluating lecturers competence in Artificial Intelligence, Technological, Pedagogical, and Content Knowledge (AI-TPACK) and identifying key influencing factors are critical steps toward ensuring effective AI integration. Purpose: This study aims to explore the predictive effect of digital competence on AI-TPACK among sports education lecturers in Indonesia. Materials and methods: A correlational survey design was employed, involving 105 lecturers from Physical Education, Health, and Recreation programs (PJKR) across five teacher education institutions in West Java. Data were collected using two structured scales: AI-TPACK and digital competence. Structural Equation Modeling (SEM) was applied to analyze the relationships between variables. Results: The analysis revealed that while lecturers demonstrated above-average digital competence, their AI-TPACK competence remained below average. A significant positive correlation (r = 0.533) was found between digital competence and AI-TPACK, with digital competence emerging as a primary predictor. These findings suggest that lecturers who are more digitally competent are also more capable of integrating AI into their pedagogical practice. Conclusions: Strengthening digital competence can be a strategic foundation for building AI-related pedagogical skills. Future training programs should integrate both technical and pedagogical components of AI, tailored to the teaching context of physical education lecturers in higher education.